Bangkit Dan Berdaya Di Masa Pandemi Covid-19 Bersama Masyarakat Desa Bowong Cindea - Andalia Andalia; Andi Almunawwarah; Putri Arafah; Wilda Wilda; Risma Mustafa; Widiyanti Widiyanti; Muntasyir Muntasyir; Fiddin Fiddin; Muhammad Asril; Riska Humaera; A. Dian Novianna; Mariana Mariana; Muhammad Amrullah; Nur Azizah; Yulianti Rahman; Muhammad Fachri; Zulkifli Zulkifli (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The community service carried out by Maros Muslim University KKN students batch V in 2022 aims to awaken and empower the Bowong Cindea village community in the midst of the covid-19 pandemic which in recent years has attacked and caused significant changes to human life around the world. In the current situation of the COVID-19 pandemic, people really need encouragement to return to being productive despite all the limitations that exist. Therefore, students as agents of change are presented in the implementation of the real work lecture program (KKN) promoted by the university to encourage the enthusiasm of the Bowong Cindea village community to remain productive during the COVID-19 pandemic through work programs carried out by KKN participants at the Muslim University of Maros.